Navigating cultural transitions during resettlement: the case of unaccompanied refugee minors - Andersson, Elin Sofia; Øverlien, Carolina (Frontiers in Psychology, 2023)
Introduction Refugees face the process of cross-cultural transitions upon arrival in their host country. This process is commonly referred to as acculturation and can be particularly challenging for asylum-seeking children and adolescent unaccompanied by a caregiver. To more effectively facilitate unaccompanied refugee minors (URMs) resettlement, this study sought to obtain an enhanced understanding of the acculturation processes of these youth’. Methods Thus, interviews with 48 URMs, all of whom arrived before the age of 16 years, were analyzed in two steps. First, how the youth described their host country’s society and culture, followed by how they navigated within this societal and cultural landscape during resettlement. Results The youth described how they navigated the Norwegian cultural and societal landscape by gaining cultural competence, adapting and finding ways to contribute, which made it easier for the youth to gain access to the society, to succeed as well as enhance their sense of agency. However, the youths also reported having to navigate between the expectations of their original and host country cultures, struggling with finding a balance between the two cultures. Discussion The youth’ acculturation processes seemed to be the result of both their own needs, wishes and behavior as well as specific features in their host country culture, which supports the notion that acculturation processes to some degree are context- and culture-dependent. Knowledge regarding the cultural and societal framework that these youth face and how they navigate within it during resettlement is critical for identifying possible cross-cultural challenges and promoting positive developmental tracks. To understand more about acculturation and integration processes, future research should include specific cultural and societal features as well as immigrants’ own perspectives and experiences during resettlement.